Evaluating a Community-Based Citizen Science Project: Attitude as a Key Mediator of Behavior Intention Toward Biodiversity Conservation - Hsu, Chia-Hsuan; Kang, Jiefeng; Yeh, Liang-Yu; Chai, Lei; Kao, Wei-Cheng; Chen, Chang-Po; Hsieh, Hwey-Lian; Lin, Hsing-Juh (Conservation, 2025)
Community-based citizen science plays a vital role in biodiversity conservation by engaging the public in scientific research while fostering environmental awareness. This study evaluates a citizen science project conducted in the Taoyuan Algal Reef (TAR) region of Taiwan, focusing on participants’ motivations, learning outcomes, and their relationship with behavioral intentions toward biodiversity conservation. Despite a small sample size, our findings provide valuable insights into the effectiveness of such initiatives. Learning and self-achievement emerged as the primary motivators for participation, with social interaction playing a secondary role. Using the structural equation model (SEM), we confirmed that attitude serves as a critical mediator between knowledge, sense of place, and behavioral intention. This supports the Knowledge-Attitude-Behavior (KAB) model, emphasizing that knowledge acquisition fosters attitudinal shifts that ultimately drive conservation behavior. Moreover, place-based learning was identified as a key component in strengthening participants’ sense of place and ecological awareness. Our findings suggest that aligning citizen science initiatives with participants’ motivations enhances engagement and long-term conservation efforts. Additionally, ongoing community monitoring not only contributes to scientific data collection but also empowers local communities in environmental decision-making. This study highlights the broader educational, social, and ecological benefits of community-based citizen science and underscores the need for systematic evaluations to optimize its impact.